Alcohol no ordinary commodity : research and public policy - Babor, Thomas (Oxford : Oxford University Press, 2010)
From a public health perspective, alcohol is a major contributor to morbidity and mortality, and impacts on many aspects of social life. This text describes advances in alcohol research with direct relevance to the development of effective policies at local, national and international level.
Previous ed.: 2003.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Alcoholism -- Government policy; Alcoholism -- Prevention; Alcoholic beverages -- Government policy